Lean against the wind: The effect of policy uncertainty on a firm's corporate social responsibility strategy - Peng, Daoju; Colak, Gonul; Shen, Jianfu (Journal of Corporate Finance, 2023)
We examine the effect of policy uncertainty on firms' strategy of corporate social responsibility (CSR). During uncertain times, firms strategically increase their commitment to CSR causes. Policy uncertainty is positively associated with CSR performance regardless of the estimation method. CSR strategy can substitute for lobbying when firms attempt to manage policy uncertainty. Improved CSR performance can reduce firms' exposure to policy uncertainty which indicates that CSR commitment can deliver insurance-like benefits. The findings highlight the value of CSR commitments during uncertain times.